Analisis Aksesibilitas Spasial Pejalan Kaki Stasiun LRT Jakarta Menggunakan Metode Isochrone - Bagas Indra Lesmana; Jericho Jericho; Mohamad Yusuf (Journal Collabits, 2026)
Pedestrian accessibility around public transportation stations is a key factor in the success of Transit-Oriented Development (TOD) systems in increasing ridership. This study measured, mapped, and analyzed pedestrian catchment areas around Jakarta LRT station corridors, with a travel time of up to 120 minutes, using the Geographic Information System (GIS) QGIS using Network Analysis and Isochrone Mapping methods. Road network data was obtained from OpenStreetMap (OSM) via the QuickOSM plugin. Analysis parameters were configured with a constant walking speed of 5 km/h (1.39 m/s) and a 5-minute time interval. The results show significant spatial disparities between stations. Rasuna Said Station (5,005 km²) and Setiabudi Station (4,182 km²) have optimal accessibility thanks to their extensive and connected arterial road networks and surrounding areas. In contrast, North Boulevard Station (0.008 km²), Velodrome (0.015 km²), and Cikoko (0.034 km²) experience spatial entrapment of pedestrians. This limitation is caused by physical barriers such as toll roads, concrete dividers, and a lack of public crossing facilities. Physical interventions are needed, including constructing pedestrian bridges (JPOs) and updating micro-spatial data on the OSM platform.